Extending borders: law and the law as discursive and ideological exercises in the everydaynes - Albornoz Barra, Gonzalo (2018)
Considering that the right and the norm are cultural productions, the critical and multidisciplinary vision in the study of law not only means a contribution linked to the world of Social Sciences and Humanities, on the contrary, multidisciplinary approaches in the study of the legal can have important social effects, helping to understand and explain more accurately the implications of the law in the daily lives of all subjects. The following pages will try to defend the idea that the right and the law are at the same time, cultural productions and control devices that operate with a dangerous freedom in the absence of a critical look at the character and effects of law in everyday life and in the representations that are built in the world.